2011
DOI: 10.1364/oe.19.005670
|View full text |Cite
|
Sign up to set email alerts
|

Mode structure of coupled L3 photonic crystal cavities

Abstract: Abstract:We investigate the energy splitting, quality factor and polarization of the fundamental modes of coupled L3 photonic crystal cavities. Four different geometries are evaluated theoretically, before experimentally investigating coupling in a direction at 30 • to the line of the cavities. In this geometry, a smooth variation of the energy splitting with the cavity separation is predicted and observed, together with significant differences between the polarizations of the bonding and anti-bonding states. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 19 publications
(20 reference statements)
2
50
0
Order By: Relevance
“…In quantum mechanics, the molecular ground state is expected to be a bonding state and the first excited state is expected to be an anti-bonding state. However, due to the oscillating nature of the evanescent waves in the photonic band gaps, as observed in other photonic systems 22,23 , and also in electronic systems 24 , in our system of coupled L0-type PC microcavities aligned at 0 degrees, the lower frequency ground state changes from bonding to anti-bonding by varying the distance between the PC microcavities, as shown in Fig. 3 (e).…”
mentioning
confidence: 73%
“…In quantum mechanics, the molecular ground state is expected to be a bonding state and the first excited state is expected to be an anti-bonding state. However, due to the oscillating nature of the evanescent waves in the photonic band gaps, as observed in other photonic systems 22,23 , and also in electronic systems 24 , in our system of coupled L0-type PC microcavities aligned at 0 degrees, the lower frequency ground state changes from bonding to anti-bonding by varying the distance between the PC microcavities, as shown in Fig. 3 (e).…”
mentioning
confidence: 73%
“…Overall, it is shown that the coupling strength of PhC photo nic molecules can be controlled using FlIJ printing simply by changing the separation of the printed strip cavities, thus overcoming limitations imposed by the discrete photonic lattice. [34] To demonstrate direct writing of a nanocavity, we explored the creation of cavities using a blank PhC template (without any waveguide). So far, related experimental demonstrations have involved selective infiltration of PhC air-holes with a lowrefractive-index fluid using a needle contacting the hole sidewall, and have opened exciting prospects for making rewritable photonic circuits [35,36] and for applications in particle sensing [37,38] or quantum optics.…”
Section: Doi: 101002/adma201704425mentioning
confidence: 99%
“…The photonic bandgap in these nano-structures allows for effective light confinement in a very small cavity volume together with low optical loss. At the same time, PhCs give easier and more flexible design ability for coupled cavities [114,115]. Therefore, coupled PhC nano-resonators present a more suitable platform for lab on-chip experiments and have also been promising for the development of fast lasers [116,117] and switchable lasers [118].…”
Section: Overviewmentioning
confidence: 99%
“…PhC devices with various geometries and structures such as hollow core PhC fibers [131], 1D and 2D waveguides [132,133] and nano-cavities [114,115,[134][135][136] have been fabricated and used for sensing applications. Among these devices, PhC cavity-based sensors offer important advantages over PhC waveguide sensors since they can be made much smaller, thus reducing vulnerability from impurities and losses.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation